THE INFORMATION SEEKING BEHAVIOUR OF THE STUDENTS OF Al IMDAD ISLAMIC BOARDING SCHOOL BANTUL AS VOTERS IN THE 2024 PRESIDENTIAL ELECTION - Marwiyah Marwiyah; Labibah Zain; Aliva Diva Kamila; Fadlan Agustina Firdaus (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2026)
A presidential election is an important national event where people use their right to vote as a form of their participation in affording a legitimate national leader. Santri is part of the community to vote in the 2024 Presidential Election. Santri are a community group that lives in an environment with distinctive characteristics such as a limited social environment, restrictions on the use of gadgets, and great obedience to kyai. This research aims to explore the students’ behavior in retrieving the information they need to vote in the election, to find out both the internal and external aspects that influence them in making their decisions. This research involves 67 informants taken from the students of Al Imdad Top Islamic High School, who have the right to vote in the 2024 Presidential Election. Data collection is done by asking open questions concerning the aspects of information searching, such as information sources, information search, information evaluation, and information use. Then the data are analyzed in 3 steps: coding, identifying the theme, pattern, and relation, and summarizing the data. The research result shows that basically the santri (students) have performed the four important aspects of information seeking but in different level of implementation. Limited access to electronic information plays a role in the process of gathering information about the presidential election. Therefore, human information sources in the santri environment, such as kyai and teachers become an alternative source and consequently, these figures influence santris in making decision. Although the students evaluate the information provided by these figures, it is less critical than it should be. This study ultimately found that santri have participated in the democratic process in Indonesia, but on the other hand, santri still need to have information literacy skills to ensure that they are able to search for, evaluate, and use information to participate in civic engagement, so that in making decisions they are not influenced by authoritative figures, but rather depend more on authoritative information sources.